Digital Transformation in Agriculture: A Field Research on Licensed Warehousing, EWR and TMEX (Third Sector Social Economic Review, 2025)
The agricultural sector has entered a digital transformation process, reshaping the entire value chain from production to marketing, storage, and finance. In Türkiye, the institutional framework of this transformation is defined by licensed warehousing (LD), electronic warehouse receipts (ELÜS), and the Turkish Commodity Exchange (TÜRİB). The aim of this study is to examine producers’ knowledge levels, intentions to use, and reasons for non-adoption of these systems.Survey data were collected from 403 hazelnut producers in the Eastern Black Sea region (Giresun, Ordu, Trabzon, and Samsun) and analyzed using ANOVA, independent samples t-test, and Chi-square tests. The findings reveal that more than half of the participants have low knowledge of LD, while nearly 70% report low knowledge of ELÜS and TÜRİB. Knowledge of LD and ELÜS significantly increases with age and farming experience, particularly among those over 56 years and with more than 21 years of experience. Gender differences are significant only for LD, with women reporting higher knowledge than men. Moreover, producers with higher knowledge levels are more likely to express future adoption intentions.The main reason for low adoption of LD and ELÜS is the absence of licensed warehouses in the region, whereas insufficient information is the leading barrier for TÜRİB. The majority of producers remain unwilling to use LD and ELÜS in the future, while adoption intentions for TÜRİB are split nearly evenly. No statistically significant relationship was found between non-adoption reasons and demographic variables such as age or farming experience, although weak latent associations were observed in some subgroups. Overall, the results are consistent with the literature emphasizing limited knowledge, traditional marketing habits, and low financial literacy as barriers to adoption.
Keywords: Digitalization in Agriculture; Licensed Warehousing; Electronic Warehouse Receipt; The Turkish Mercantile Exchange; Agricultural Finance